Child psychology : - Vasta, Ross (John Wiley, 1995)
This updated topically organized text examines child psychology from the perspectives of three principal traditions which characterize the discipline today--the cognitive-developmental, environmental-learning and ethological orientations. It emphasizes the very latest issues and findings including the microgenetic research method, gene therapy, psychoteratology, the social bases of early memory and family contributions to peer relations. This edition contains social policy applications, 1000+ new references and end-of-chapter questions designed to foster critical thinking.